Struktur Naratif Tokoh Utama dalam Film "Hajjan" berdasarkan Model Aktansial dan Fungsional A.J. Greimas - Putri Aulia Tauziah; Wildan Taufiq; Khomisah Khomisah (Dzil Majaz: Journal of Arabic Literature, 2026)
This study aims to analyze the narrative structure of the main character in the film Hajjan using the actantial model and the functional structure proposed by A.J.Greimas. This Saudi Arabian film, released in 2023, has been screened at various festival and in several countries, including Canada, Saudi Arabia, the United States and Germany. The film tells the story of Matar, a Bedouin teenager who strives to continue his deceased brother’s struggle and save his beloved camel through the competitive and conflict-ridden world of camel racing. This his study employs a qualitative descriptive method using Greimas’s semiotic approach. Data was collected through observation and note-taking, specifically by repeatedly watching the film’s dialogues and scenes and then recording relevant data using the actantial model and functional structure. The results indicate that the film’s narrative is constructed through Matar’s journey toward achieving his goals, which evolve alongside the plot. This study confirms that the film functions not only as entertainment but also as a narrative work built through characters, conflicts, and the achievement of goals that shape the story’s meaning